THE EFFECTIVENESS OF SEX EDUCATION HEALTH PROMOTION MEDIA IN INCREASING REPRODUCTIVE HEALTH KNOWLEDGE IN STUDENTS OF SMK MEDIKA SAMARINDA - Johan, Herni; Noorbaya, Siti; Yuniar, Dewi (Proceeding of International Conference on Multidisciplinary Research, 2024)
The influence of the spread of stimulation (pornography) through the sexual environment which causes the bad character of teenagers to be formed from this environment and the lack of information about the dangers of free sex through audio-visual brochures and others. This research aims to compare the influence of various health promotion media (leaflets, comics, and Whatsapp group applications) in increasing students' knowledge about the dangers of free sex at SMK Medika Samarinda. The research design uses a quasi-experiment, namely pretest and posttest control group design to determine differences in knowledge that occur due to the influence of treatment (intervention). Data were analyzed using a paired difference test (paired sample t-test) with SPSS. The research results showed that the comic plus counseling method was the most effective in increasing students' knowledge with an increase in scores of 5.46 points. Meanwhile, the counseling plus leaflet method increased teenagers' knowledge scores by 2.53 points and counseling plus WhatsApp groups given to teenagers was able to increase teenagers' knowledge scores about free sex by 2.70 points. The best method is counseling plus comics because it can change the highest knowledge value. The use of comics as a media for health education for teenagers needs to be developed to prevent teenagers from the bad effects of free sex and also to form WhatsApp groups for teenagers as well as health education content, especially the bad effects of free sex.